(untitled) (Palíndromo, 2013)
This research seeks different ways to think about curatorship in contemporary art. The main proposition that guided the thinking in this research was the principle composition investigated by Warburg and had as main result the Mnemosyne’s Atlas. This composition, present at various conferences, written and Atlas proposed by Warburg in the 20s, this study sought to bring his ideas to contemporary art. For this approximation, the choice b exhibition 31th Panorama of Brazilian Art was made by unique and effective way to accomplish curated by Adriano Pedrosa.